2017
DOI: 10.2147/jaa.s96153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a sublingual immunotherapy solution in olive-induced respiratory allergy in Jordan: a retrospective observational study

Abstract: BackgroundOlive pollen is an important cause of respiratory allergy in the Middle East. In this study, the clinical characteristics of adults and children with confirmed allergic rhinitis (AR; with or without asthma) in Jordan were described, and the use of sublingual immunotherapy (SLIT) in a real-life clinical setting was assessed.MethodsThis retrospective observational study evaluated the clinical features of olive-induced allergy and the use of an SLIT solution of standardized extracts toward Ole e 1 given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The current study found 36.6% of participants had seasonal allergies, which is consistent with the prevalence of seasonal allergies in Jordan and is associated with exposure to pollen from olive trees [33]. The current study showed that seasonal allergies did not significantly affect tinnitus.…”
Section: Discussionsupporting
confidence: 87%
“…The current study found 36.6% of participants had seasonal allergies, which is consistent with the prevalence of seasonal allergies in Jordan and is associated with exposure to pollen from olive trees [33]. The current study showed that seasonal allergies did not significantly affect tinnitus.…”
Section: Discussionsupporting
confidence: 87%